INTESTINAL PARASITES OF SPOTTED MURREL CHANNA PUNCTATUS, AND POPULATION DYNAMICS RELATED TO MONTH AND HOST SEX - N. VINATHA (The Bioscan, 2011)
Monthly variations and the effects of host sex on parasite population dynamics were examined in spotted murrel (Channa punctatus). This study was carried out for a period of one year (July 2000 – June 2001). A total of 233 fish were examined. Two helminth parasitic species were identified in intestine of the fish viz., Palisentis nagpurensis, Lytocestus indicus. The analysis of the data showed that the helminth parasites showed a cyclic variability and seasonal periodicity in their occurrence with reference to host sex.